Bouwhistorisch onderzoek van de voormalige abdijschuur van Ter Doest (Bulletin KNOB, 2005)
For building historians the shed of the former Cistercian monastery Ter Doest, founded in 1174, has acquired the status of a place of pilgrimage. In Flanders there is not much evidence left of the agricultural land area of this monastic order. After having flourished during the Middle Ages, gradual decay followed for Ter Doest as well.The dilapidated abbey buildings were eventually reused as building material. The shed survived because it was used for the further exploitation of the farm. The building has a rectangular ground plan of approximately 54 metres long and 20 metres wide, with a ridge height of approximately 16.5 metres. By means of stylistic and typological comparison the building date was so far estimated at 1275/80.Building-historical research was carried out in connection with the recent restoration of the shed. All the wood joints of the oak roof are mortise and tenon joints, fixed with wooden nails. The only exceptions are the halved joints of rafters and loft. The geometrical proportions of the roof are also to be found in the crosscut façades. From research into the assembly marks it appeared that the main spars were numbered from south to north and that the spars of the rafters consist of two groups, which recur in the assembly marks of the wind braces.The four northern bays have a different numbering system from the five southern ones. The roof may have been constructed in two phases. Previous attempts to arrive at a dendrochronological dating of the roof did not produce any result. Within the scope of our research new wood samples were taken.Most of them failed to show a significant growth pattern and the sapwood had disappeared due to centuries of erosion processes. This made dating extremely difficult and the calculations were tested against those of a number of Bruges roofs from the same period. By combining all the results it was possible to conclude that the wood had been cut down in the period from 1370 to 1385.This is more than a century later than the earlier notion that the shed originated from around 1280. The masonry research shows that the body of the façades is regular and that no large alterations have been carried out since the time of its construction. However, there are numerous irregularities or anomalies around the existing openings, which indicates that many of them were made later or were altered.Originally the main entrance was in the crosscut façades. Later a passage was added in the longitudinal wall, at the place where there used to be a traverse building. From test excavations it appeared that the foundations of roof and walls were laid independent from each other. The posts of the roof are placed on individual footings, which widen underground.The foundation of the longitudinal walls contains Gothic arches. The recent research made it possible to solve a lot of questions and remove a few mysteries. However, a new problem has also arisen, notably the discord between the dating of the roof and the characteristics and typology of brick architecture. Thanks to this new problem the shed continues to arouse building historians' interest, which in itself is a good thing.